Inhibicion de la produccion de aflatoxinas por diversos insecticidas - Miguel, J.A.=700 1 De Andres, V.; Carballo, M.
(Es, En)
ilus., 23 ref.
Keywords: INHIBICION; AFLATOXINAS; ASPERGILLUS FLAVUS; INSECTICIDAS; EFECTOS RESIDUALES; TOXICIDAD; ESPAÑA